2020
DOI: 10.1111/jdv.16264
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine glands are bystanders in hidradenitis suppurativa and their involvement is gender specific

Abstract: BackgroundApocrine glands have been long considered as the initial targeted skin compartment in hidradenitis suppurativa/acne inversa (HS).ObjectiveDetection of apocrine gland involvement in HS.MethodsApocrine glands were isolated from skin biopsies of involved and uninvolved skin of HS patients (n = 16, females : males 1 : 1) by laser capture microscopy and studied by whole transcriptome profiling. Dysregulated genes were detected by comparing lesional and non‐lesional skin obtained from female and male HS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…[78][79][80] This is further perpetuated through leucocytekeratinocyte interactions, [78][79][80] further amplifying antimicrobial peptide and chemokine production (including CXCL1 and CXCL8), 81 leading to further inflammatory cell recruitment adjacent to IL-17eactivated epidermal keratinocytes (Fig 3). Such inflammatory cell localization has been observed surrounding intrafollicular and interfollicular sites adjacent to epidermal keratinocytes in early histologic specimens of hidradenitis suppurativa, [9][10][11]64 with evidence of early psoriasiform hyperplasia suggestive of IL-17einduced epidermal changes.…”
Section: T-helper Cell 17 Feed-forward Inflammation Is Prominent In Ementioning
confidence: 65%
“…[78][79][80] This is further perpetuated through leucocytekeratinocyte interactions, [78][79][80] further amplifying antimicrobial peptide and chemokine production (including CXCL1 and CXCL8), 81 leading to further inflammatory cell recruitment adjacent to IL-17eactivated epidermal keratinocytes (Fig 3). Such inflammatory cell localization has been observed surrounding intrafollicular and interfollicular sites adjacent to epidermal keratinocytes in early histologic specimens of hidradenitis suppurativa, [9][10][11]64 with evidence of early psoriasiform hyperplasia suggestive of IL-17einduced epidermal changes.…”
Section: T-helper Cell 17 Feed-forward Inflammation Is Prominent In Ementioning
confidence: 65%
“…In contrast, histopathologic and molecular studies indicate significant involvement of the hair follicle with secondary apocrine gland injury. [156][157][158][159] There are a number of changes in the hair follicle including an occluding spongiform inflammation in the infundibulum with predominantly T cells and infundibular disintegration in early lesions. 157,160 Hair follicle keratinocytes also produce more proinflammatory cytokines and have an altered pattern of antimicrobial peptide production.…”
Section: Hair Folli Cle S Tem Cell Replic Ation Disorder Vs Alopementioning
confidence: 99%
“…Their findings indicated that in contrast to the entire lesional skin in HS patients, an inflammatory signal was not prominent in the apocrine glands. The key dysregulated pathway in female lesional skin was the androgen signaling pathway and in males was the lipid metabolism pathway, reflected in gender-specific transcriptomes 13 .…”
Section: Epidemiologymentioning
confidence: 99%